"Ein neues Lied" - Weber, Beat (Biblische Notizen, 2009)
The expression Xdx ryX “a new song” occurs in the OT in Isa 42,10; Ps 33,3; 40,4; 96,1; 98,1; 144,9; 149,1. This contribution focuses not on the newness as such but on the contrast to an earlier song which the phrase may imply. It is argued that the “new songs” relate back to Ex 15,1-18.21, Israel’s archetypical response to the primary act of redemption. This song has been adapted and transformed to celebrate the continuity of the acts of YHWH in creation and history.